2010
DOI: 10.3386/w16215
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Miscalibration

Abstract: Using a unique 10-year panel that includes more than 13,300 expected stock market return probability distributions, we find that executives are severely miscalibrated, producing distributions that are too narrow: realized market returns are within the executives' 80% confidence intervals only 36% of the time. We show that executives reduce the lower bound of the forecast confidence interval during times of high market uncertainty; however, ex post miscalibration is worst during periods of high uncertainty. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 30 publications
7
120
1
3
Order By: Relevance
“…The few longitudinal studies suffer from sporadic sampling and relatively few judgments (Ben-David et al 2013, Dunlosky and Rawson 2012, Simon and Houghton 2003. In the current study, we examine probabilistic forecasts of important events over a period of three years.…”
Section: Effects Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…The few longitudinal studies suffer from sporadic sampling and relatively few judgments (Ben-David et al 2013, Dunlosky and Rawson 2012, Simon and Houghton 2003. In the current study, we examine probabilistic forecasts of important events over a period of three years.…”
Section: Effects Over Timementioning
confidence: 99%
“…Overconfidence affects the judgments of physicians (Oskamp 1965), entrepreneurs (Cooper et al 1988), bridge players (Keren 1987), government planners (Flyvbjerg et al 2002), investors (Statman et al 2006), and basketball players (Jagacinski et al 1977), to name but a few examples. Research has identified overconfidence in tests of declarative knowledge, bets, and predictions of the future (Ben-David et al 2013, Massey et al 2011. Perhaps it should come as no surprise that forecasts of geopolitical events, so central to intelligence analysis and policy formulation, are also biased by overconfidence (Gardner 2010, Silver 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the area that he gravitated towards, bounded rationality, is hardly taught in courses on economic theory. 11 We avoid the term SG&O that pre…xes Herbert Simon's in ‡uence on this approach because we believe that the KT&O program has also been in ‡uenced by it. Indeed, Herbert Simon was appreciative of the procedural rationality and highlighted the ecological rationality of heuristics.…”
Section: The Ktando Approachmentioning
confidence: 99%
“…The G&O approach identi…es Herbert Simon's bounded rationality approach as its intellectual fountainhead and there is a large number of contributors to it. 11 G&O have focussed on 9 See, for instance, the entertaining panel discussion on behavioral economics at the 2011 Lindau Nobel Laureate Meeting in Economic Sciences. The participants were George A. Akerlof, Robert J. Aumann, Eric S. Maskin, Daniel L. McFadden, Edmund S. Phelps, and Reinhard Selten.…”
Section: The Ktando Approachmentioning
confidence: 99%
“…Housing market speculation by out-of-town second-home buyers is also unprofitable (Chinco and Mayer (2012)) and leverage may play an important role (Ben-David (2011) and Haughwout et al (2011)). Even companies with overconfident managers have higher debt leverage (Ben-David et al (2013)). …”
mentioning
confidence: 99%